Chemical and microbiological characteristics of waste material from fishponds in Republic of Macedonia - Belichovska Katerina, Belichovska Daniela, Petrov Petar, Duraku Suzana (Slovak Environment Agency, Tajovskeho 28, 975 90 Banska Bystrica, SLOVAKIA, 2016)
In order to preserve the natural ecological balance of aquatic ecosystems, there is a strong need for prevention of loading the surface and groundwater from contamination by material derived from fishponds. For thispurpose, chemical and microbiological tests of raw and thermally processed waste material were conducted from three fishponds in Republic of Macedonia. It was found that raw waste material was not contaminated with harmful compounds, heavy metals and pesticides, but contained a lot of microorganisms which makeit unusable.In thermally processed waste material there were hardly any harmful microorganisms and the total number of bacteria was reduced to a minimum. This suggests that thermally processed waste material from fishponds can be used as a supplement to animal food and for other purposes.
Keywords: waste material, fishpond, chemical and microbiological characteristics